Peran Narrative Marketing Memoderasi Pengaruh Influencer Marketing, Sosial Media Marketing, Kualitas Pelayanan terhadap Keputusan Menginap - Komang Yadura Arya; Kadek Adyatna Wedananta; Made Ratih Nurmalasari; Ida Nyoman Basmantra (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Bali’s rapid growth in private villa tourism has intensified competition among accommodation providers, where similar villa concepts often result in differing occupancy levels. This gap indicates that digital marketing strategies may influence guests’ stay decisions in varying ways. This study investigates the effects of influencer marketing, social media marketing, and service quality on stay decisions, and examines the moderating role of narrative marketing in strengthening these relationships. A quantitative explanatory design was applied using purposive sampling, involving 94 respondents who had stayed at Magic Hills Villa in Karangasem, Bali. Data were obtained through an online questionnaire using a ten-point Likert scale and analyzed with Structural Equation Modeling Partial Least Squares (SEM-PLS). The analysis included assessments of validity, reliability, and hypothesis testing through bootstrapping. The results show that influencer marketing, social media marketing, and service quality each exert a positive and significant influence on stay decisions. Narrative marketing significantly reinforces the effect of influencer marketing but does not moderate the influence of social media marketing or service quality. These findings highlight that authentic storytelling enhances the persuasive impact of influencers, while guest experiences and social media interactions remain primarily shaped by service encounters and platform dynamics.